Effects of Pilates exercises on idiopathic scoliosis: a scoping review of the literature - KURU ÇOLAK, TUĞBA (My University, 2023)
Purpose Scoliosis is a deformity involving changes in three planes. These changes include lateral curvature in the frontal plane, changes in physiological thoracic kyphosis and lumbar lordosis angles in the sagittal plane, and rotation of the vertebrae in the transverse plane. The aim of this scoping review was to review and summarize the available literature to determine whether Pilates exercises are an efective treatment for scoliosis. Methods The Cochrane Library (reviews, protocols, trials), PubMed, Web of Science, Ovid, Scopus, PEDro, Medline, CINAHL (EBSCO), ProQuest, and Google Scholar electronic databases were used to search for published articles from inception to February 2022. All the searches included English language studies. Keywords were determined as “scoliosis and Pilates” or “idiopathic scoliosis and Pilates”, “curve and Pilates”, “spinal deformity and Pilates.” Results Seven studies were included; one study was a meta-analysis study, three studies compared Pilates and Schroth exercises, and three applied Pilates exercises in combined therapy. The studies included in this review used outcome measurements of Cobb angle, ATR, chest expansion, SRS-22r, posture assessment, weight distribution, and psychological factors such as depression. Conclusions The results of this review suggest that the level of evidence regarding the efect of Pilates exercises on scoliosisrelated deformity is very limited. Pilates exercises can be applied to reduce asymmetrical posture in individuals with mild scoliosis with reduced growth potential and progression risk.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Scoliosis; Spine; Pilates; Exercise